Giving a combination of Tubifex sp feed and floating pellets for the growth and survival of kelabau fish fry (Osteochilus melanopleurus, Bleeker 1852) - Asiah, Nur; Aryani, Aryani; Riauwaty, Morina (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
The research was conducted from April to August 2023 at the Fish Hatchery and Breeding Laboratory. Faculty of Fisheries and Marine Sciences, University of Riau. The purpose of this study was to determine the effect of changing Tubifex sp natural feed with floating pellets on the growth and survival of kelabau fish larvae. The method used in this study was an experimental method with one factor using a completely randomized design (CRD) with nine treatments and 3 replications. The treatments given were P1 (8 gr Tubifex sp and 2 gr floating pellets), P2 (7 gr Tubifex sp and 10 gr floating pellets), P3 (6 gr Tubifex sp and 4 gr floating pellets), P4 (5 gr Tubifex sp and 5 gr floating pellets), P5 (4 gr Tubifex sp and 6 gr floating pellets), P6 (3 gr Tubifex sp and 7 gr floating pellets), P7 (2 gr Tubifex sp and 8 gr floating pellets), P8 (1 gr Tubifex sp and 9 gr floating pellets) and P9 (10 gr floating pellets) each treatment was carried out for 10 days. The analysis used in this research is descriptive analysis. The results showed that there was an effect of combined feeding on the growth of kelabau fish as indicated by an increase in absolute weight and length. Absolute weight and length decreased when using floating pellet feed, this is suspected pellet feed is not in accordance with the eating habits of kelabau fish.